Impact of Land Use Change on Land Capability in Katingan Regency, Central Kalimantan, Indonesia - Beni Iskandar; Fathul Zannah; Rifqi Ansari (UIR PRESS, 2023)
The imbalance between land use and land capability can cause environmental problems in Katingan Regency. This study aims to analyze changes in land use change for the 2015-2021 period, land capability, land cover suitability with land capability in Katingan Regency. This research uses the method of overlaying the 2015 and 2021 land cover maps, analyzing land capability with variables of erosion maps, flood maps, and aridity maps, and analyzing land suitability by overlapping land use maps and land capability maps. The results show that land use change is 67.864 ha with map accuracy KA = 90.6% and OA 81.1%, while the concentration of land use change in Malan Island District with an LQ value of 2.5. Land capability is divided into three with the limiting factors of erosion, flooding, and slope class, namely: class II, III, IV, VI, and VII which are designated as productive paddy fields, dry land agriculture, and agriculture mixed with shrubs. Land use change has an impact on land capability, namely the increase of unsuitable land by 23.050 ha. This research can provide important information for taking policies and strategies for optimizing land use at the site level in Katingan Regency in the future.